Dependence of cell proliferation on the morphology of starch based scaffolds for tissue engineering - Chung, S. (2008)
[Excerpt] In tissue engineering (TE), several biological, mechanical and geometrical design constraints need to be addressed in order to create an adequate micro-environment for cells response. In this study, the correlation between architectural features of the scaffold construct and cellular behavior was investigated for a blend of starch and polycaprolactone (SPCL). The aim was to determine the effects of scaffold parameters on mechanical properties on cell seeding efficiency and proliferation of human osteoblast-like cells (SaOs-2) of scaffolds obtained via Rapid Prototyping (Bioplotter) and fiber bonding. For fiber bonding, a L8 design of experiment approach was used to produce different scaffold morphologies and properties by systematically varying processing parameters. [...]